Morphological characteristics and aloin production in polyploid plants of Aloe vera (L.) Burm. F. (Asphodelaceae) (Bioagro, 2020)
Aloe vera is a medicinal species that has been in great demand for the properties of its secondary metabolites, such as aloin. However, the slow plant growth rate and low quantity of this metabolite in its biomass has made it necessary to search for strategies that improve the quality of the plant. The objective of this work was to determine the morphological characteristics and aloin content in polyploidized aloe vitroplants from seven populations in Venezuela. The values ​​of height, number of leaves and width of the leaf, dry mass, concentration and aloin production were higher in polyploid plants of all populations compared to diploid controls. Similarly, highly significant differences were found between polyploid populations. The plants from locality of Carazao showed the highest mean values ​​of aloin concentration (7.69 %) and production (0.169 g per 100 g dry weight) in response to artificial chromosomal duplication. The growing of these new genotypes could improve the utilization of aloe at a commercial and industrial level, and the new knowledge shows the potential of induced polyploidy as a rapid means to improve morphological characteristics and production of secondary metabolites in crops.
Keywords: Aloe plant; In vitro; plant morphology; polyploidy